Phosphorylation coexists with O‐GlcNAcylation in a plant virus protein and influences viral infection. (30th January 2018) - Martínez‐Turiño, Sandra; Pérez, José De Jesús; Hervás, Marta; Navajas, Rosana; Ciordia, Sergio; Udeshi, Namrata D.; Shabanowitz, Jeffrey; Hunt, Donald F.; García, Juan Antonio
Summary: Phosphorylation and O‐ GlcNAcylation are two widespread post‐translational modifications (PTMs), often affecting the same eukaryotic target protein. Plum pox virus (PPV) is a member of the genus Potyvirus which infects a wide range of plant species. O‐ GlcNAcylation of the capsid protein (CP) of PPV has been studied extensively, and some evidence of CP phosphorylation has also been reported. Here, we use proteomics analyses to demonstrate that PPV CP is phosphorylated in vivo at the N‐terminus and the beginning of the core region. In contrast with the 'yin–yang' mechanism that applies to some mammalian proteins, PPV CP phosphorylation affects residues different from those that are O ‐GlcNAcylated (serines Ser‐25, Ser‐81, Ser‐101 and Ser‐118). Our findings show that PPV CP can be concurrently phosphorylated and O‐ GlcNAcylated at nearby residues. However, an analysis using a differential proteomics strategy based on iTRAQ (isobaric tags for relative and absolute quantitation) showed a significant enhancement of phosphorylation at Ser‐25 in virions recovered from O ‐GlcNAcylation‐deficient plants, suggesting that crosstalk between O ‐GlcNAcylation and phosphorylation in PPV CP takes place. Although the preclusion of phosphorylation at the four identified phosphotarget sites only had a limited impact on viral infection, the mimicking of phosphorylation prevents PPV infection in Prunus persica and weakens infection in Nicotiana benthamiana and other herbaceous hosts, prompting the emergence of potentially compensatory second mutations. We postulate that the joint action of phosphorylation and O ‐GlcNAcylation in the N‐proximal segment of CP allows a fine‐tuning of protein stability, providing the amount of CP required in each step of viral infection.